Les mémoires d’une automobile (pas) comme les autres. La Coccinelle VW et ses mises en histoire - Pierre LANNOY (Conserveries Mémorielles)
This article aims at providing a sociological account of a bulk of heterogeneous materials including narratives of the history of the famous car from Volkswagen, ‘The Beetle’. In order to do that, it proposes a typology of the ways these historical narratives are socially organized through so-called memorial channels. These are conceived as made of several components : specific devices for the historical accounting of the Beetle’s past, particular modes by which this car became an object-of-a-certain-practice, distinct versions of its nature and genealogy. The article then details four memorial channels by which the Beetle is given a history : a hagiographic channel, in which it becomes an object of passion, being unique in the automotive history ; an academic channel, in which it is seized as an object of research calling for epistemologically founded interpretations ; a political channel, in which the Beetle calls for moral judgments on the part of culturally situated individuals ; an iconic channel, transforming it in a semiotic object feeding aesthetic interpretations. The never-ending social practices which make these channels active give to the VW Beetle its mythic stuff and its peculiar place in the cultural landscape of Western societies.